Agent-based simulation of pedestrian dynamics for exposure time estimation in epidemic risk assessment - Harweg, Thomas; Bachmann, Daniel; Weichert, Frank (Technische Universität Dortmund, 2021)
Purpose With the coronavirus disease 2019 (COVID-19) pandemic spreading across the world, protective measures for containing the virus are essential, especially as long as no vaccine or effective treatment is available. One important measure is the so-called physical distancing or social distancing. Methods In this paper, we propose an agent-based numerical simulation of pedestrian dynamics in order to assess the behavior of pedestrians in public places in the context of contact transmission of infectious diseases like COVID-19, and to gather insights about exposure times and the overall effectiveness of distancing measures. Results To abide by the minimum distance of 1.5 m stipulated by the German government at an infection rate of 2%, our simulation results suggest that a density of one person per 16m2 or below is sufficient. Conclusions The results of this study give insight into how physical distancing as a protective measure can be carried out more efficiently to help reduce the spread of COVID-19.
Journal of public health;Vol. 31. 2022, Issue 2, pp 221-228
Keywords: SARS-CoV-2; COVID-19; Pedestrian dynamics; Agent-based simulation; Social-force model; Numerical simulation; 004